Identifikasi Tumbuhan sebagai Repellent terhadap Nyamuk : Review - Lestari, Sri Wahyuni Budi (Biocaster : Jurnal Kajian Biologi, 2024)
Indonesia as one of the tropical countries in the world with high air humidity triggers the breeding of mosquitoes such as Aedes aegypti which is one of the vectors of Dengue Hemorrhagic Fever (DHF). This type of research is a literature study using the literature review method. This method is carried out by evaluating, interpreting and explaining the ideas discussed in several studies by searching for sources from the Google Scholar database. The selection of the type of article is based on the year of publication, the article can be accessed in its entirety, and discusses plants as repellents against mosquitoes. Based on research results from several sources, there is a biological prospect as an anti-mosquito agent for anti-mosquito and repellent/repelling power because it contains bioactive compounds, such as alkaloids, saponins, flavonoids, phenols, tannins, steroids and terpenoids. These compounds enter through respiratory contact and digestive/gastric toxins so that mosquitoes experience mortality/death. This compound also blocks chemical receptors (chemoreceptors) found on the palpus and antennae of mosquitoes, so that mosquitoes escape without sucking blood again. It is hoped that this review article can provide information regarding repellent plants as anti-mosquitoes. It can be concluded from the results of the review that there are plants that have repellent power against Aedes aegypti with increased protective power according to the increase in concentration of the plant used, as well as the length of exposure of the extract from each plant to the skin.